Urgensi Penggunaan Sistem Informasi Manajemen dalam Pemasaran - Muhammad Abdillah Alwi; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2024)
This research aims to briefly explain the urgency of using management information systems in marketing a product or service. This research uses qualitative methods with a library research approach. The research results show that the application of information technology for marketing needs is very important because it can significantly increase the options available to companies and plays an important role in the effective implementation of each element of marketing strategy, can influence the marketing strategy development process because information technology provides more things and information to managers through the use of decision-making systems, information technology has the ability to integrate various different parts of the organization and provide a lot of information to managers, and information technology also influences the organization's interface with the environment.